Desempenho de fibrocimentos extrudados produzidos com fibras e nanofibrilas de juta - Fonseca, Camila Soares (2016)
An alternative to fiber-cement production is the extrusion, which allows many advantages to the production of cementitious composites with different geometries and requires a low initial investment for industrial production. In this context the objective of this project was to evaluate the performance of fiber and jute nanofibrils as reinforcement in fiber-cement composites. The jute fibers were subjected to alkali treatment with NaOH to remove non-cellulose components. From the suspension of fibers treated with NaOH, the nanofibrils have been generated through 30 cycles of defibrillation of the vegetable fibers in a grinder supermasscolloider. The jute fibers before and after pre-treatment and after mechanical defibrillation in nature (control), those treated with NaOH, and nanofibrils were characterized about: chemical, thermal, crystallographic and morphological properties. Composites extruded with 0.5%, 1.0% and 2.0% (by mass) of the resultant nanofibrils were compared with composites made with the same proportions of the original jute fibers. Additionally, the substitution of jute fibers by different percentages of jute nanofibrils (0%, 25%, 50%, 75% and 100%) was analyzed. The composites produced were subjected to 28 days of curing, to natural aging and to aging in a controlled environment before being analysed about their physical, static and dynamic bending, and microstructural characterization. Composites with nanofibrils showed higher water absorption and apparent porosity than the other formulations. In general, the cementitious composite that showed higher mechanical performance was hybrid-reinforced with 1.5% of nanofibrils and 0.5% of fibers, probably because of the synergetic work of these two types of reinforcement. The dynamic modulus of the naturally aged composites increased gradually over time, showing that the fiber-cements became stiffer with weathering exposure.